Surgery 101 Podcast: Episodes 31-40 - Jonathan White; Nishan Sharma; Cian OKelly; Max Findlay; Dan Schiller; Allan Ho; David Saliken; Stewart Hamilton (Association of American Medical Colleges, 2011)
Abstract This resource is a series of podcasts intended to serve as brief introductions to and reviews of surgical topics for medical students. Each topic is around 15 minutes long so that learners can quickly grasp the basic concepts relating to a common surgical problem. Learning objectives are provided for each episode; episodes are divided into chapters and conclude with several key points to summarize the topic. The topics in this module cover coma, subarachnoid hemorrhage, intracerebral hemorrhage, carotid stenosis, otolaryngology, diverticular disease, periampullary and pancreatic cancers, rectal cancer basics, missed appendicitis, and compartment syndrome. Surgery 101 has been produced since October 2008; it was created by Dr. Parveen Boora and Dr. Jonathan White and is currently produced by the Undergrad Surgery Mobile Podcasting Studio Team with the assistance of the members of the Surgery Department at the University of Alberta. We recommend that episodes be provided to students before a seminar to allow them to quickly get to grips with basic information on a topic. That way, time in face-to-face teaching can be spent applying knowledge to specific clinical scenarios. Students can also listen to the podcasts during dedicated study time, while reviewing before an examination, while on call, and while travelling or exercising. We have also used the podcasts within a seminar format, with students and presenters listening to the podcast together and discussing the topics raised.